1996
DOI: 10.1007/bf00210785
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel serum protein binding with high affinity to alpha1-acid glycoprotein

Abstract: The binding of docetaxel to human plasma proteins was studied by ultrafiltration at 37 degrees C and pH 7.4. Docetaxel was extensively (> 98%) plasma protein bound. At clinically relevant concentrations (1-5 micrograms/ml), the plasma binding was concentration-independent. Lipoproteins, alpha1-acid glycoprotein and albumin were the main carriers of docetaxel in plasma, and owing to the high interindividual variability of alpha1-acid glycoprotein plasma concentration, particularly in cancer, it was concluded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 7 publications
8
84
2
Order By: Relevance
“…Increased AAG resulted in a decreased Slope value. This relationship was also expected since docetaxel is extensively bound to AAG, and this is mainly responsible for interindividual variability in docetaxel unbound fraction (f u ) (Urien et al, 1996). In the present NONMEM analysis, the Slope values link total plasma docetaxel concentrations and neutropaenic responses.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Increased AAG resulted in a decreased Slope value. This relationship was also expected since docetaxel is extensively bound to AAG, and this is mainly responsible for interindividual variability in docetaxel unbound fraction (f u ) (Urien et al, 1996). In the present NONMEM analysis, the Slope values link total plasma docetaxel concentrations and neutropaenic responses.…”
Section: Discussionsupporting
confidence: 52%
“…However, the relationship between the Slope values and the AAG level does not lead to dosing recommendations based on the AAG level. Indeed, several studies have confirmed that the docetaxel CL is dependent on f u , with a lower CL in patients with high AAG levels (Urien et al, 1996;Baker et al, 2005). Interindividual variability in AAG is not associated with marked changes in the AUC of free docetaxel.…”
Section: Discussionmentioning
confidence: 95%
“…The one-step LLE was proved to be simple, rapid and successful with an average recovery ratio of about 89-91% for docetaxel at the tested concentrations Table 2 Recovery of docetaxel was found to be less as the drug is highly protein bound (~ 97%). 8,9 Hence the % RSD for recoveries was found to be all below 8%. The possibility of matrix effect caused by ionization competition between the analytes and the endogenous co-eluents was evaluated at three QC concentrations in triplicate.…”
Section: Recovery and Matrix Effectmentioning
confidence: 92%
“…The plasma protein binding rate of docetaxel was >90%, while that of thio-TEPA was <15%; docetaxel rarely passes through the renal corpuscle, while thio-TEPA is easily excreted. 19,20 Docetaxel or thio-TEPA dissolved in DMEM with 10% FBS was circulated throughout the circulation channel to assay its anticancer activity with the system.…”
Section: Bioassay Of Anticancer Agents With the Systemmentioning
confidence: 99%